Cochrane Database of Systematic Reviews 2009
DOI: 10.1002/14651858.cd004197.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic strategies for eradicating Pseudomonas aeruginosa in people with cystic fibrosis

Abstract: We found that nebulised antibiotics, alone or in combination with oral antibiotics, were better than no treatment for early infection with Pseudomonas aeruginosa. Eradication may be sustained in the short term. Overall, there is insufficient evidence from this review to state which antibiotic strategy should be used for the eradication of early Pseudomonas aeruginosa infection in CF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 52 publications
3
75
0
4
Order By: Relevance
“…In contrast, compelling evidence of a clinical benefit in CF with early intervention is very scarce [3], and it has been suggested that young CF patients with early infection with P. aeruginosa often have minimal symptoms and mild lung disease, which may lead to insensitive outcome measures [35]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, compelling evidence of a clinical benefit in CF with early intervention is very scarce [3], and it has been suggested that young CF patients with early infection with P. aeruginosa often have minimal symptoms and mild lung disease, which may lead to insensitive outcome measures [35]. …”
Section: Discussionmentioning
confidence: 99%
“…Early detection of infection with P. aeruginosa in patients with CF may be important as certain antibiotic treatments have proven useful in preventing or delaying chronic bronchial infection with P. aeruginosa [2]. Although the most effective treatment has yet to be determined, eradication of P. aeruginosa seems more likely using strategies with nebulised antibiotics [3]. …”
Section: Introductionmentioning
confidence: 99%
“…P. aeruginosa infection has been associated with 48 : Worse lung function outcomesHigher respiratory tract inflammationA greater risk of respiratory exacerbationsHigher risk of mortality…”
Section: Cf Microbiologymentioning
confidence: 99%
“…This can be prevented by early detection and treatment [3, 4]. As a significant proportion of patients with new P. aeruginosa infection remain asymptomatic [5], microbiological surveillance is vital to ensure that it is not missed.…”
Section: Introductionmentioning
confidence: 99%